High-throughput Screening and Biosensing with Fluorescent C. elegans Strains - Leung, Chi K. (MyJove Corporation, 2011)
High-throughput screening (HTS) is a powerful approach for identifying chemical modulators of biological processes. However, many compounds identified in screens using cell culture models are often found to be toxic or pharmacologically inactive in vivo(1-2). Screening in whole animal models can help avoid these pitfalls and streamline the path to drug development. C. elegans is a multicellular model organism well suited for HTS. It is small (<1 mm) and can be economically cultured and dispensed in liquids. C. elegans is also one of the most experimentally tractable animal models permitting rapid and detailed identification of drug mode-of-action(3). We describe a protocol for culturing and dispensing fluorescent strains of C. elegans for high-throughput screening of chemical libraries or detection of environmental contaminants that alter the expression of a specific gene. Large numbers of developmentally synchronized worms are grown in liquid culture, harvested, washed, and suspended at a defined density. Worms are then added to black, flat-bottomed 384-well plates using a peristaltic liquid dispenser. Small molecules from a chemical library or test samples (e.g., water, food, or soil) can be added to wells with worms. In vivo, real-time fluorescence intensity is measured with a fluorescence microplate reader. This method can be adapted to any inducible gene in C. elegans for which a suitable reporter is available. Many inducible stress and developmental transcriptional pathways are well defined in C. elegans and GFP transgenic reporter strains already exist for many of them(4). When combined with the appropriate transgenic reporters, our method can be used to screen for pathway modulators or to develop robust biosensor assays for environmental contaminants. We demonstrate our C. elegans culture and dispensing protocol with an HTS assay we developed to monitor the C. elegans cap ‘n’ collar transcription factor SKN-1. SKN-1 and its mammalian homologue Nrf2 activate cytoprotective genes during oxidative and xenobiotic stress(5-10). Nrf2 protects mammals from numerous age-related disorders such as cancer, neurodegeneration, and chronic inflammation and has become a major chemotherapeutic target(11-13).Our assay is based on a GFP transgenic reporter for the SKN-1 target gene gst-4(14), which encodes a glutathione-s transferase(6). The gst-4 reporter is also a biosensor for xenobiotic and oxidative chemicals that activate SKN-1 and can be used to detect low levels of contaminants such as acrylamide and methyl-mercury(15-16).